Strategi Dakwah pada Kelas Menengah Muslim di Indonesia: Pendekatan Marketing Dakwah dan Islam Rasional - Affandy, Shofyan (STID Al-Hadid, 2025)
DA’WAH STRATEGIES FOR THE MUSLIM MIDDLE CLASS IN INDONESIA: DA’WAH MARKETING AND RATIONAL ISLAM APPROACHES. The development of the Muslim middle class in Indonesia has generated both opportunities and challenges for Islamic da‘wah. This segment is characterized by relatively high levels of education, rational competencies, modern lifestyles, and extensive access to digital media. Conventional da‘wah approaches, which are predominantly ethical–normative in orientation, have not been fully able to address the specific needs of the Muslim middle class. This article aims to develop a conceptual model of da‘wah strategy for the Indonesian Muslim middle-class segment through a rational Islam–based da‘wah marketing approach. The study employs a qualitative-conceptual research based on a systematic conceptual literature review on the essence of da'wah, the characteristics of the Muslim middle class, Islamic rationality, and marketing theory. SWOT analysis is used as a synthetic framework to map the strengths, weaknesses, opportunities, and threats of da‘wah among the Muslim middle class, in order to formulate contextual da‘wah strategies and programs. The rational Islam approach, which integrates revelation, reason, and social context, is identified as a strategic foundation for the development of da‘wah targeting the Muslim middle class. By integrating the characteristics of the Muslim middle class, rational Islam, and analysis of the da‘wah environment, this study proposes a conceptual model of rational Islam–based da‘wah marketing as a framework for developing effective and solution-oriented da‘wah within Indonesian Muslim society. This study enriches da‘wah discourse through a strategic–epistemological perspective and offers a practical reference for da‘wah managers in designing relevant and sustainable da‘wah strategies and programs amid the dynamics of Indonesia’s modern Muslim middle class.